Cation‐Directed Isomerization of the U28 Uranyl‐Peroxide Cluster. Issue 46 (1st December 2017) - Oliveri, Anna F.; Colla, Christopher A.; Callahan, Joseph R.; Bogard, Gwendolyn; Qiu, Jie; Dembowski, Mateusz; Burns, Peter C.; Casey, William H.
Abstract: Invited for the cover of this issue are Anna Oliveri from Southern Oregon University, USA, and co‐workers. The cover image shows the outer surface of a nanoscale U28 cage cluster. Abstract : The work is relevant because of the need to remediate stockpiles of radioactive waste, some of which will reach the biosphere… Read more about the story behind the cover in the Cover Profile and about the research itself in theCommunication by A. F. Oliveri et al.